STUDY OF TECHNOLOGY FOR THE RELIABILITY AND SURVIVABILITY MODELLING OF ONBOARD CONTROL SYSTEM OF SMALL SPACECRAFT OPERATING IN COMPLEX MODES - Pavlov, Alexander N.; Pavlov, Dmitry A.; Kulakov, Alexander Yu.; Zakharov, Valerii V. (Journal of Applied Engineering Science, 2024)
The technology of system modeling of reliability and survivability of the onboard control system (OCS) of the spacecraft is presented in the study of various options for the activation of operating modes. The technology of spacecraft functioning based on the concept of digital twins currently takes a leading position. That’s concept allows you to create realistic virtual copies of spacecraft, to simulate not only the objects themselves, but also the processes of their design and operation in various conditions of a priori uncertainty. Such conditions, first of all, should include the destructive effects of an aggressive external environment (outer space) and the multi-mode nature (sequence and intensity of the modes involved) of the functioning of onboard spacecraft systems. The implementation of the requirements of multi-purpose and multi-mode control in these conditions is closely related to the study of the reliability and survivability of such objects from the standpoint of considering their structural construction. The proposed article discusses an approach to assessing the reliability and survivability of onboard systems of small spacecraft (SS), which is based on the concept of a parametric genome structure, taking into account the multi-mode operation in an aggregated form.
Keywords: modes of functioning, parametric genome of structure, structural and functional survivability, motion control system, small spacecraft, onboard control complex